Microbiological profile and biofilm formation on removed intrauterine contraceptive devices from a sample of Egyptian women. Issue 6 (June 2014) - Abdel‐Hafeez, Mohamed; El‐Mehallaway, Nabegh; Khalil, Ibrahim; Abdallah, Fatma; Elnaggar, Ahmed
Abstract Aim The aim of this study was to investigate the presence of biofilm formation around intrauterine contraceptive devices (IUCD) and to correlate the microbiological profile of the IUCD‐associated genital infections to the microbiological profile of specimens retrieved from vaginal discharge. Material and Methods Samples of the vaginal discharge in the posterior fornix were collected from 50 women attending the Family Planning Clinic in Ain Shams University Hospital using two high vaginal swabs. Swabs were immediately sent for Gram staining as well as microbiological culture. The IUCD was then removed. A 0.5‐cm piece of the removed IUCD was cut and sent for culture. Growing colonies were tested for their abilities to form a biofilm (colorimetric method). Another 0.5‐cm piece of the removed IUCD was examined by electron microscopy (EM) for detection of biofilm formation. Results Among the included 50 women, 24 (48%) women showed biofilm formation (via colorimetric methods). EM scanning was able to detect biofilm formation in the prepared pieces of the removed IUCD of 48 (96%) women. There was no significant agreement between the isolated microorganisms on the removed IUCD and the vaginal swab (proportion of agreement was 14 [11.4%]; κ = −0.089, P = 0.892). Conclusion Scanning EM is a useful tool in detection of biofilm formation on removed IUCD.